Potential Antidiabetic Compounds from Anogeissus leiocarpus: Molecular Docking, Molecular Dynamic Simulation, and ADMET Studies - Mubarak Muhammad Dahiru; Neksumi Musa; AbdulAzeez Mumsiri Abaka; Maimuna Abdulrahman Abubakar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aimed to evaluate the antidiabetic potential of compounds from Anogeissus leiocarpus in silico and the potential of the compounds as antidiabetic drug candidates. Molecular docking (MD), molecular dynamics simulation (MDS), and ADMET were carried out in silico to evaluate the compounds' antidiabetic potential and drug candidacy. The MDS revealed the least BA (-8.7 kcal/mol) was exhibited by compound X (palmitic acid) with Glucagon-like Peptide-1 Receptor (GLP1), while the highest BA (-5.8 kcal/mol) was demonstrated by I (1,2,4-benzetriol) with dipeptidyl peptidase IV (DPP-4) among the best interactions. The MDS result showed good docked complexes' flexibility, deformability, and stability with low eigenvalues ranging from 8.52 × 10-5 to 1.30 × 10-4. All the compounds had a bioavailability score of 0.55 except VI (0.85), while the synthetic ability showed a good score of ≤3.01. Eight compounds were predicted to be soluble, with two poorly soluble. Additionally, all the compounds had high gastrointestinal absorption, with the majority being blood-brain barrier permeant, while skin permeation value was between -2.55 and -7.48 cm/s. Furthermore, none of the compounds were either permeability glycoprotein (P-gp) substrate or CYP2C19 and CYP2C9 inhibitors, though some were CYP1A2, CYP2D6, and CYP3A4 inhibitors. Moreover, the toxicity study showed moderate to non-toxicity results with toxicity classes between 3 and 5. Conclusively, the compounds from A. leiocarpus showed good binding interactions, which are the protein targets of antidiabetic therapy and potentially good candidates for antidiabetic drug development.